2004
DOI: 10.1176/appi.ajp.161.3.515
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Transcranial Magnetic Stimulation of the Right Dorsolateral Prefrontal Cortex in Posttraumatic Stress Disorder: A Double-Blind, Placebo-Controlled Study

Abstract: This double-blind, controlled trial suggests that in PTSD patients, 10 daily sessions of right dorsolateral prefrontal rTMS at a frequency of 10 Hz have greater therapeutic effects than slow-frequency or sham stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
201
2
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(217 citation statements)
references
References 76 publications
8
201
2
6
Order By: Relevance
“…Accordingly, we determined whether rTMS, a well-established therapeutic method PTSD treatment, offered benefits as early intervention after stress. Prior studies have indicated that administration of high-frequency rTMS to the right dorsolateral prefrontal cortex is beneficial for ameliorating PTSD symptoms [26,27]. Our data presented herein demonstrated for the first time that chronic administration of rTMS has anxiolytic effect on stressrelated anxiety-like behaviors without affecting control rats.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Accordingly, we determined whether rTMS, a well-established therapeutic method PTSD treatment, offered benefits as early intervention after stress. Prior studies have indicated that administration of high-frequency rTMS to the right dorsolateral prefrontal cortex is beneficial for ameliorating PTSD symptoms [26,27]. Our data presented herein demonstrated for the first time that chronic administration of rTMS has anxiolytic effect on stressrelated anxiety-like behaviors without affecting control rats.…”
Section: Discussionsupporting
confidence: 58%
“…Therefore, non-pharmacologic treatment approaches have been developed. Repetitive transcranial magnetic stimulation (rTMS) is a safe and non-invasive method, and studies have indicated that administration of high-frequency rTMS to the right dorsolateral prefrontal cortex is beneficial for ameliorating PTSD symptoms [26,27]. Although it was primarily utilized for treatment, we hypothesized that rTMS might also provide benefits as an early prevention measure.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings of a higher HPA-system sensitivity in more anxious individuals after HF-rTMS applied over the right DLPFC might be especially germane in light of the therapeutic applications of rTMS as a treatment for anxiety disorders and/or posttraumatic stress disorder (PTSD) (Cohen et al, 2004;Pallanti and Bernardi, 2009;Zwanzger et al, 2009;Handwerger, 2009;Yue et al, in press). Because of the overwhelming evidence that GABAergic mechanisms regulate neuroendocrine stress responses (Herman et al, 2002;Herman et al, 2004;Kovács et al, 2004;Cullinan et al 2008;Radley et al, 2009) and the importance of GABA receptor involvement in the pathophysiology and treatment of anxiety disorders (Lydiard, 2003;Nemeroff, 2003;Kalueff and Nutt., 2007), it is tempting to assume that in our study the observed HPA-axis sensitivity to one HF-rTMS session in more anxious females was mediated by the GABA system.…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, the neurobiological modulation of stress responses seems to be lateralized to the right prefrontal cortex [14]. Animal models also indicate that stress-regulatory systems such as the HPA-axis are predominantly regulated by the right prefrontal cortex [54].…”
Section: Discussionmentioning
confidence: 99%